Facilitating and Regulating Commerce - White, Douglas (Victoria University of Wellington Law Review, 2002)
This article explores how Sir Ivor Richardson's Court of Appeal approached the facilitation and regulation of commerce in the areas of competition and securities law from 1977 to 2002. The author explores the introduction of key legislation (Commerce Act 1986, Fair Trading Act 1986, Securities Amendment Act 1988, and the Companies Act 1993) alongside the establishment of the Securities Commission and Commerce Commission. The article then discusses how competition law was explored through cases involving the record industry, primary production, telecommunications, and electricity transmission. The Court of Appeal's approach to securities law and economics is also explored. It is concluded that Sir Ivor's impact on law and economics is the realisation that market participants cannot be left unregulated and unrestrained to pursue the maximisation of their own wealth. The above legislation are the principal constraints – day-to-day responsibility and administration being left to the Commissions, while courts would interpret and apply the legislation in individual cases in a manner which reflects the underlying economic and social policies.